A Permanent Magnet Generator for Energy Conversion from Marine Currents: No Load and Load Experiments. (28th June 2012) - Thomas, Karin; Grabbe, Mårten; Yuen, Katarina; Leijon, Mats
Abstract : This paper presents experiments and measurements on a low speed permanent magnet cable wound generator for marine current energy conversion. Measurements were made for no load and nominal load (4.44 Ω/phase) conditions at nominal speed (10 rpm). For either load condition, the magnetic fields in the air gap were also measured. The measurements on the generator were compared with the corresponding finite element method simulations used to design the machine. It is shown in the paper that measurements and corresponding case simulations show good agreement. At nominal speed, the measured and simulated load voltages (nominal load) differ less than 1% for the rms values and less than 5% for peak values. At no load, measured and simulated voltages had larger differences, that is, <9% for rms values and <5% for peak values. Harmonic analyses of measured and simulated phase voltages and currents show only the presence of third harmonics. The percentage of harmonics in the measured data was comparable with the corresponding predictions of the simulations. The discussions and results presented in the paper could be beneficial for future design of efficient and reliable marine current energy converter systems.